TRICHODERMA HARZIANUM: ADSORPTION, DESORPTION, ISOTHERM AND FTIR STUDIES - A. Shoaib; N. Aslam; N. Aslam (Journal of Animal and Plant Sciences, 2013)
Metal removal capability of indigenous soil fungus of Pakistan i.e. Trichoderma harzianum (Rifai) was determined through laboratory bioassays. Experiments were conducted in flasks by taking 0.1 g of powdered fungal biomass in 100 mL (25 mg/L) of metal solution kept at 150 rpm for 3 hours. Results showed that the biomass of T. harzianum exhibited significantly greater adsorption efficiency of 65% (capacity: 16.33 mg/g) for uptake of Cr(VI) ions from the aqueous solution. FTIR spectroscopy of the fungal biomass revealed the involvement of chitin and chitosan in metal adsorption process. Adsorption efficiency was significantly decreased (70-50%) and capacity increased (15-50 mg/g) with increase in Cr(VI) concentration from 20, 40…….100 mg/L. Batch data was well-defined by Langmuir and Freundlich isotherms. Solution pH evaluated in the range of 2, 4…..10 found to favor adsorption at pH 2 (efficiency: 70%, capacity 50 mg/g). Adsorption/desorption trials using four acids indicted, maximum desorption of metal was occurred with HNO3 (qdes: 10 mg/g) followed by HCl (9 mg/g), CH3COOH (8 mg/g) and H2SO4 (7 mg/g). Adsorption based trials summarized that dried powdered biomass of T. harzianum is suitable and easily available indigenous biomaterial with viable application in the removal of Cr(VI) from the metal-bearing solution within the concentration of 20-100 mg/L.
Keywords: Heavy metal; Cr (VI); waste water; adsorption; Fungus; Trichoderma harzianum